Fast Times During Spring Breaks: Are Traffic Fatalities Another Consequence? - Michael French; Gulcin Gumus (Institute for the Study of Labor (IZA), 2014)
Every year in the United States, millions of college students travel for spring break, spending billions of dollars. We examine a potential adverse consequence of spring break that has received little attention in the literature - traffic safety. In particular, we estimate the impact of spring break season on fatal passenger vehicle crashes. Using daily county-level longitudinal data on traffic fatalities in popular spring break destinations from 1982-2011, we conduct separate analyses by age groups, license status, and alcohol involvement in the crash. Our findings indicate that passenger vehicle fatalities are significantly overrepresented during the spring break season.
Keywords: I12; I18; H73; 330; spring break; college students; traffic fatalities; externalities